Association between ErbB4 gene function in synaptogenesis and schizophrenia pathogenesis. Issue 1 (1st January 2020) - Li, Ranli; Chen, Min; Tian, Hongjun; Li, Gongying; Wang, Lina; Tu, Wenzhen; Chen, Guangdong; Ping, Jing; Zhuo, Chuanjun; Li, Jie
Abstract: This study investigated the role of ErbB4, the schizophrenia susceptibility gene, in synaptogenesis and synaptic transmission and its association with the pathogenesis of schizophrenia. We found that there was no significant difference in the size of inhibitory synapsin Gephyrin clusters in the dendrites of gamma-aminobutyric acid (GABA) neurons in the cultured cortex of ErbB4 knockout (ErbB4−/−) mice and ErbB4+/+ mice. The density and area of PSD-95 clusters in GABA-labelled neurons were not significantly different from those in the control group ( p > 0.05). Specific pIkBα labelling of the pyramidal neurons and the axon initiation segments showed that the number of neuronal dendrites and the inhibitory postsynaptic proteins Gephyrin in the ErbB4 knockout group were significantly lower than those in the control group, whereas the size of the Gephyrin cluster remained unchanged. The number and area of the VGAT clusters on the somaclonal and axonal surfaces of the pyramidal neurons were also similar. ErbB4 knockout influenced excitatory synapses in intermediate neuronal cells and inhibitory synapses in pyramidal neurons, however, did not affect the inhibitory synapses in intermediate neuronal cells and excitatory synapses in pyramidal neurons. The number and area of PSD-95 clusters on the neuronal surface were significantly lower than those of the 1NMPP1 group, but the number and area of Gephyrin clusters on the neuronal surface were not changed ( p > 0.05). These findings demonstrated that ErbB4 gene had no effect on the inhibitory synapses in interneurons and the excitatory synapses in pyramidal neurons.